Market Orientation in Optimizing Supply Chain Strategy to Improve the Performance of Manufacturing Companies - Purba, Okin Ringan; Abdurachman, Edi; Setiawan, Edhie Budi; Nofrisel, Nofrisel (Institut Transportasi dan Logistik Trisakti, 2025)
This study aims to examine the impact of supply chain strategy on the performance of manufacturing companies, incorporating competitive advantage and market orientation as mediating variables. In the increasingly competitive global market, manufacturing companies face significant challenges in maintaining and improving their performance. One of the key factors influencing a company's success is an effective supply chain strategy. However, the interaction among supply chain strategy and other factors such as competitive advantage and market orientation in enhancing company performance remains underexplored. The research was conducted in the Province of DKI Jakarta, where data was collected from 323 employees of manufacturing companies through a questionnaire with 33 Likert-scale indicators (1-5). The data was analyzed using PLS-SEM software to test eight hypotheses. The results indicate that supply chain strategy has a positive and significant impact on company performance. Competitive advantage and market orientation are proven to be strong mediators, reinforcing the impact of supply chain strategy on company performance. These findings suggest that an effective supply chain strategy not only enhances operational efficiency but also strengthens the company's competitive position and responsiveness to the market. The implications of this study emphasize the importance of manufacturing company management focusing not only on supply chain efficiency but also on the development of market orientation and competitive advantage. This can provide strategic guidance for companies in enhancing their competitiveness and performance in an increasingly competitive market.